Marketing network and profitability of cut flower for Mexicali Valley, Baja California, Mexico - Samaniego-Gámez, Blancka Yesenia; Cano-García, Gloria Virginia; Colinas-León, María Teresa Beryl; Sánchez-Abarca, Carlos; Manzo-González, Alejandro (Revista Mexicana de Ciencias Agrícolas, 2018)
Cut f lower commercialization for Baja California contributed during 2004 with more than 122 million pesos, considering f lower seed and cut f lower production. Most of cut f lowers produced in state of Baja California Norte is for export market, by this reason local market means an opportunity for introducing quality products at market prices from national companies. Mexicali city, by being near USA and together with its population economic wealth thanks to profitability of cotton and orchards production in Mexicali Valley, is one or the main producer region in the country. By this reason and thanks to great amount of f lower shops located in the region the aim of describingmarketingnetworkandprofitabilityforcutflower in Mexicali Valley is proposed. Market study and diagnose to make FODAanalysis were developed, defining strategies in order to seize economic potential. Actual distribution networks and marketing system consist in moving cut f lowers from production centers, Córdoba, Veracruz and Coatepec de Harinas district, state of Mexico, up to Mexicali Valley, Baja California, keeping quality and optimum vase life for final customer, also proper planning for production chain due not covered demand along year it is required, the population has economical potential and tradition to give flowers guaranteeing good profitability. Roses (Rosa gigantea and R. chinensis L.), asian lilies (Lilium spp.), chrysanthemum [Dendranthema x grandiflorum (Ramat) Kitamura c. v. Polaris White], carnation (Dianthus caryophyllus), gerbera (Gerbera jamesonii H. Bolux ex Hook F.) and oriental lilies (Lilium spp.) are species with more consumers’ interest.
Keywords: FODA analysis; productive chain; marketing; economical potential; flower production